A development program for novice teachers: the UnB IsF NucLi experience - Lourenço, Rachel (Olhares & Trilhas, 2019)
This article is the result of a study carried out at the Núcleo de Línguas do Programa Idiomas sem Fronteiras (IsF NucLi) of the University of Brasília (UnB) during the period 2017-2018. The teacher development actions at the UnB IsF NucLi for the Idiomas sem Fronteiras (IsF) or Languages without Borders (LwB) Program were investigated by means of two questionnaires answered by former and by current participants, which contained questions about novice teachers' perceptions of the training they had received or were receiving and the impacts of this training on their professional lives. In general terms, the answers of former and current participants were similar. The most often mentioned areas for both groups were classroom management, lesson planning, and course design. They also mentioned critical thinking skills, collaborative work and a supportive environment. Despite being designed for novice teachers, this training program was not limited to the development of basic, daily teaching skills, so it was actually a teacher development or teacher education program, which focused on long-term professional development and on equipping novice teachers with tools that would aid them in decision-making processes along their careers.